2014
DOI: 10.3109/15563650.2014.909601
|View full text |Cite
|
Sign up to set email alerts
|

Poisonings requiring admission to the pediatric intensive care unit: A 5-year review

Abstract: Pediatric poisonings are a significant percentage of admissions to the PICU. The majority of poisonings are non-fatal, require supportive care, close monitoring, and some specific treatment. Drug classes causing poisonings have changed to a higher percentage of opioids in younger patients and atypical antidepressants in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
44
2
27

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 13 publications
9
44
2
27
Order By: Relevance
“…These findings agree with those of previous studies that reported significant associations between male gender and unintentional poisoning and female gender and intentional poisoning. 7,14–18 Higher rate of self-harm in adolescent females was reported by previous studies and it was explained by higher tendency of internalizing emotional and behavioral problems in female adolescents. 19,20 Moreover, previous studies on gender differences in suicide attempts report that females tend to use non-violent methods such as asphyxia by carbon monoxide poisoning, drug toxicity, and alcohol toxicity while males tend to use more violent methods like firearms or jumping from a height.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These findings agree with those of previous studies that reported significant associations between male gender and unintentional poisoning and female gender and intentional poisoning. 7,14–18 Higher rate of self-harm in adolescent females was reported by previous studies and it was explained by higher tendency of internalizing emotional and behavioral problems in female adolescents. 19,20 Moreover, previous studies on gender differences in suicide attempts report that females tend to use non-violent methods such as asphyxia by carbon monoxide poisoning, drug toxicity, and alcohol toxicity while males tend to use more violent methods like firearms or jumping from a height.…”
Section: Discussionmentioning
confidence: 81%
“…These findings are consistent with the results of previous epidemiologic studies on pediatric poisoning, which found a bimodal age distribution of poisoning, with a high incidence among toddlers and a second peak during adolescence. 614 …”
Section: Discussionmentioning
confidence: 99%
“…[11] Childhood poisoning exposures are almost always accidental. [14] Deliberate poisoning in children is unlikely to be reported to poison centres. A more accurate estimate of the prevalence of intentional poisoning in infants would be obtained from hospital admissions, as well as those from primary healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Even ve ark. (37) zehirlenme olgusunun % 8'inin çocuk yoğun bakımda izlendiğini, bunlardan yalnızca birinin kaybedildiğini gözlemişlerdir. Yılmaz (9) % 0,4, Öntürk (10) % 0,6, Genç (15) % 0,7, Özdemir (30) % 0,9 mortalite bildirmişlerdir.…”
Section: Discussionunclassified